Star Formation Histories of Dwarf Galaxies from the Colour-Magnitude Diagrams of Their Resolved Stellar Populations - Michele Cignoni; Monica Tosi (Advances in Astronomy)
In this tutorial paper we summarize how the star formation (SF) history of a galactic region can be derived from the colour-magnitude diagram (CMD) of its resolved stars. The procedures to build synthetic CMDs and to exploit them to derive the SF histories (SFHs) are described, as well as the corresponding uncertainties. The SFHs of resolved dwarf galaxies of all morphological types, obtained from the application of the synthetic CMD method, are reviewed and discussed. To summarize: (1) only early-type galaxies show evidence of long interruptions in the SF activity; late-type dwarfs present rather continuous, or gasping, SF regimes; (2) a few early-type dwarfs have experienced only one episode of SF activity concentrated at the earliest epochs, whilst many others show extended or recurrent SF activity; (3) no galaxy experiencing now its first SF episode has been found yet; (4) no frequent evidence of strong SF bursts is found; (5) there is no significant difference in the SFH of dwarf irregulars and blue compact dwarfs, except for the current SF rates. Implications of these results on the galaxy formation scenarios are briefly discussed.